Travel route advisor with artificial neural network (TRAANN) / Aznuf Hafeez Kaswuri - Aznuf Hafeez , Kaswuri (2003)

(untitled)
The aim of this project is to develop a Travel Route Advisor, which apply Artificial Neural Network ANN). The system has the ability to predict the most efficient solution of the available routes. The first chapter is the introduction. It give an overview of the project. It describes the objectives scope and limitation of the project. Chapter 2 is for the literature review. It contains a review of studies done in related fields. It includes some studies in artificial intelligence and artificial neural networks as well. Chapter 3 is about system methodology. It describes the steps taken to accomplish this project and development method taken. Chapter 4 is for system analysis, which cover the system requirements and the project schedule. Chapter 5 is about system design. It includes the design of the system proposed. It contains the core modules of the system, namely database, ANN and GUI modules.Chapter 6 is for the system implementation. It describes the trans formation of the modules into programming code. Chapter 7 is for system testing. Tests had been made to verify whether the system have met the requirements.The discussion chapter, which is chapter 8, contains the discussion on the result , the problem encountered, the solution taken and the conclusion of the project.